2015
DOI: 10.1590/2237-6089-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of cognitive rehabilitation for bipolar disorder

Abstract: Introduction: It has been shown that bipolar disorder (BD) has a direct impact on neurocognitive functioning and behavior. This finding has prompted studies to investigate cognitive enhancement programs as potential treatments for BD, primarily focusing on cognitive reinforcement and daily functioning and not restricted to psychoeducation and coping strategies, unlike traditional psychosocial treatments. Objective: This study presents a systematic review of controlled trials of cognitive rehabilitation (CR) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, a systematic review on previous studies found no robust evidence regarding effectiveness of cognitive rehabilitation for bipolar disorder [15]. This may be the result of intervening in populations with different CR levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, a systematic review on previous studies found no robust evidence regarding effectiveness of cognitive rehabilitation for bipolar disorder [15]. This may be the result of intervening in populations with different CR levels.…”
Section: Introductionmentioning
confidence: 99%